Educational administration theory, research, and practice - Hoy, Wayne K. (McGraw-Hill, 2001)
"Educational Administration: Theory, Research, and Practice, Sixth Edition, presents a comprehensive treatment of theory and research as they affect the day-to-day administration of schools. New case studies challenge readers to apply their knowledge to real-life school problems. The social systems approach is used to synthesize the four basic elements of schools and the processes of administration. This text provides an excellent tool and resource for students of educational administration to develop practical skills essential in today's schools."--Jacket.